Transformasi Digital dan Cicil Emas dalam Pengembangan Nasabah BSI KCP Lumajang Imam Bonjol pada Tahun 2023-2025 - Izzatul Ulya; Nurul Safitri; Kholivia Lailatus Safaah; Mariah Ulfah (YASIN, 2026)
The rapid development of digital banking services and increasing public interest in sharia-based investment products, particularly gold, indicate the importance of examining digital transformation and the Cicil Emas product in encouraging customer growth. This study aims to analyze the implementation of digital transformation at BSI KCP Lumajang Imam Bonjol, examine the development of the Cicil Emas product, and assess the contribution of both to customer growth during the 2023–2025 period. This study used a qualitative approach based on field research. Data were collected through observation and interviews with a supervisor and pawning marketing staff. The results showed that digital transformation through the BYOND by BSI application made it easier for customers to access banking services anytime and anywhere. The Cicil Emas product also showed important development supported by a hybrid marketing strategy through direct socialization, WhatsApp Business, and social media, as well as the designation of BSI as a gold bank by the government. In addition, the number of customers at BSI KCP Lumajang Imam Bonjol increased consistently, with approximately 1,452 new customers added in 2023 and 2,139 new customers added in 2024, bringing the current total number of accounts to around 14,000. Thus, digital transformation and the development of the Cicil Emas product together contributed to improving service accessibility, public trust, and the growth of the customer base at BSI KCP Lumajang Imam Bonjol.